2009
DOI: 10.1002/app.31322
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid) and zeolite composites prepared by melt processing: Morphological and physical–mechanical properties

Abstract: Poly(lactic acid), PLA, composites containing 0, 1, 3, and 5 wt % zeolite type 4A were prepared using extrusion/injection compounding techniques. Morphological characterizations were carried out by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Physical properties were evaluated by differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) and mechanical properties by standard tensile testing. The morphological studies showed a homogenous dispersion of zeolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
5
33
0
3
Order By: Relevance
“…Whatever the porous inorganic filler, at 3 wt%, they did not affect the tensile strength of the biocomposite [39]. These observations are opposite to those reported by Yuzay et al [60] for similar filler content added to neat PLA to remove or absorb offflavours and odours [61]. They found that 1% of zeolite, with an average particle size of 1-2 !m, did not modify the stiffness and the tensile strength whereas a higher content (3 or 5 wt% of zeolites) improves these mechanical characteristics of the material (+20%).…”
Section: Mechanical Properties Of the Biocompositesmentioning
confidence: 71%
See 1 more Smart Citation
“…Whatever the porous inorganic filler, at 3 wt%, they did not affect the tensile strength of the biocomposite [39]. These observations are opposite to those reported by Yuzay et al [60] for similar filler content added to neat PLA to remove or absorb offflavours and odours [61]. They found that 1% of zeolite, with an average particle size of 1-2 !m, did not modify the stiffness and the tensile strength whereas a higher content (3 or 5 wt% of zeolites) improves these mechanical characteristics of the material (+20%).…”
Section: Mechanical Properties Of the Biocompositesmentioning
confidence: 71%
“…They found that 1% of zeolite, with an average particle size of 1-2 !m, did not modify the stiffness and the tensile strength whereas a higher content (3 or 5 wt% of zeolites) improves these mechanical characteristics of the material (+20%). They attributed this behaviour to a good enough interfacial adhesion between zeolites and PLA matrix and dispersion of zeolites in PLA [60]. .…”
Section: Mechanical Properties Of the Biocompositesmentioning
confidence: 99%
“…Pode-se sugerir que a concha atuou reforçando a matriz de PEAD. A presença de partículas atuando como reforço em matrizes poliméricas tem sido reportada por outros autores [15,[17][18][19][20][21] usando zeolita, hidroxiapatita, fibras, talco, argilas, etc, sendo esse aumento da rigidez atribuído a maior transferência de força aplicada a matriz para as partículas [22][23][24][25]. Alguns autores [20,21,23] estudaram o efeito do tratamento superficial de partículas de celulose, partículas de talco com silano no módulo de armazenamento dos compósitos, obtendo melhoramento considerável, por exemplo, Abdelmouleh et al [20,21] atribuíram este efeito às interações entre o silano e os monômeros das resinas poliéster insaturado e epóxi.…”
Section: Análise Termo Dinâmico Mecânica (Dma)unclassified
“…Essa equação sugere que a adição de partículas rígidas diminui o pico de dissipação de energia, devido ao decréscimo na fração de volume da matriz, esse decréscimo tem sido mostrado na literatura [22][23][24].…”
Section: Análise Termo Dinâmico Mecânica (Dma)unclassified
“…Similarly to Biswas et al [14,15], Balkose et al [7,12,18] used the composition dependence of mechanical properties to estimate interactions in polypropylene/zeolite composites and found that they are weak. Other groups [19,20] used SEM micrographs to evaluate interfacial adhesion and based on the fact that on fracture surfaces the filler is covered by the polymer they claim strong adhesion even when the surface of the zeolite was treated with aliphatic carboxylic acids [19] that are known to decrease surface energy and interactions [21].…”
Section: Introductionmentioning
confidence: 99%